Uji Toksisitas Akut dan Subakut Pada Pemberian Ekstrak Etanol Bawang Tiwai (Eleutherine Americana Merr.) (Journal of Tropical Pharmacy and Chemistry, 2013)
The ethanolic extract from the bulb of Eleutherine americana was investigated for acute and subacute toxicity in Balb/C male mice. The parameter used on this research is mortality n hepar  histophatological. During acute toxicity study, bulb plant (0.52, 0,26 and 5.2 mg/kg b.wt) p.o. for 72 hour and subacute toxicity study bulb plant (0.52, 0,26 and 5.2 mg/kg b.wt) p.o. once daily for 30 days. The result of the research shows that ethanol extract with 0.52, 0,26 and 5.2 mg/kg b.wt dosage can be said relatively safe because there is no death signal about 50% in 24 hour and the result of subacute toxicity in observation histophatological in hepar shows there is fibrosis n necrosis with 0.52, 2.6 mg/kg b.wt and 5.2 mg/kg b.wt dosage.